PENERAPAN BALANCED SCORECARD SEBAGAI TOLAK UKUR KINERJA PERUSAHAAN PADA PT ASURANSI JASA INDONESIA (JASINDO) - Sella Gusti Pratiwi; Isma Coryanata (JURNAL FAIRNESS, 2023)
This study aims to see the performance at PT. Jasindo Insurance, Bengkulu City, using a balanced scorecard approach as a performance measure. There must be four perspectives in implementing the balanced scorecard. The sample of this study were employees / employees of PT. Jasindo Insurance, Bengkulu City, with 52 people and 163 insurance-related company customers. Data were analyzed using IBM SPSS version 20 analysis. The results of PT. Jasindo Insurance, Bengkulu City, shows that the overall result Performance appraisal of PT. Jasindo Insurance, Bengkulu City, using the balanced scorecard approach as a whole shows very well.